Proton Pump Inhibitors Decrease Soluble fms-Like Tyrosine Kinase-1 and Soluble Endoglin Secretion, Decrease Hypertension, and Rescue Endothelial Dysfunction. Issue 3 (March 2017) - Onda, Kenji; Tong, Stephen; Beard, Sally; Binder, Natalie; Muto, Masanaga; Senadheera, Sevvandi N.; Parry, Laura; Dilworth, Mark; Renshall, Lewis; Brownfoot, Fiona; Hastie, Roxanne; Tuohey, Laura; et al.
Abstract : Preeclampsia is a severe complication of pregnancy. Antiangiogenic factors soluble fms-like tyrosine kinase-1 (sFlt-1) and soluble endoglin are secreted in excess from the placenta, causing hypertension, endothelial dysfunction, and multiorgan injury. Oxidative stress and vascular inflammation exacerbate the endothelial injury. A drug that can block these pathophysiological steps would be an attractive treatment option. Proton pump inhibitors (PPIs) are safe in pregnancy where they are prescribed for gastric reflux. We performed functional studies on primary human tissues and animal models to examine the effects of PPIs on sFlt-1 and soluble endoglin secretion, vessel dilatation, blood pressure, and endothelial dysfunction. PPIs decreased sFlt-1 and soluble endoglin secretion from trophoblast, placental explants from preeclamptic pregnancies, and endothelial cells. They also mitigated tumor necrosis factor-α–induced endothelial dysfunction: PPIs blocked endothelial vascular cell adhesion molecule-1 expression, leukocyte adhesion to endothelium, and disruption of endothelial tube formation. PPIs decreased endothelin-1 secretion and enhanced endothelial cell migration. Interestingly, the PPI esomeprazole vasodilated maternal blood vessels from normal pregnancies and cases of preterm preeclampsia, but its vasodilatory effects were lost when the vessels were denuded of their endothelium. Esomeprazole decreased blood pressure in a transgenic mouse model where human sFlt-1 was overexpressed in placenta. PPIs upregulated endogenous antioxidant defenses and decreased cytokine secretion from placental tissue and endothelial cells. We have found that PPIs decrease sFlt-1 and soluble endoglin secretion and endothelial dysfunction, dilate blood vessels, decrease blood pressure, and have antioxidant and anti-inflammatory properties. They have therapeutic potential for preeclampsia and other diseases where endothelial dysfunction is involved. Abstract : Supplemental Digital Content is available in the text.